Correlation of Body Mass Index and Orthostatic Hypotension in Patients with Hypertension on ACE Inhibitor Monotherapy - Tasić, Danijela; Kovačević, Zorana; Mitrović, Miroslav; Maksimović, Zlatko; Lončar-Stojiljković, Dragana; Tasić, Nebojša (Scripta Medica, 2021)
Background/Aim: Orthostatic hypotension (OH) is considered to be a drop in the systolic and diastolic blood pressure (> 20 mmHg; > 10 mmHg) 3 minutes from postural changes. The objective of this study was to analyse the correlation of body mass index (BMI) and OH during the treatment with trandolapril, as a single-drug treatment of hypertension. Methods: The study involved 255 patients (average age 54.3 ± 11.7; 54.1 % men) with poorly regulated hypertension, who were given trandolapril as a single-drug treatment. The patients were divided into two groups regarding stage of hypertension: first-degree arterial hypertension (140-149 mmHg for systolic and 90-109 mmHg for diastolic blood pressure) and second-degree arterial hypertension (> 150 for systolic and > 110 mmHg for diastolic blood pressure). Incidence of OH occurrence was then analysed regarding hypertension stage and BMI during 6 months of follow-up, on 4 control examinations. Results: During 24-week period after trandolapril introduction into the treatment of hypertension, a statistically significant difference in systolic, diastolic and mean blood pressure values was observed. No statistically significant difference was observed in incidence of OH between the first and second as well as between third and fourth examination during the study. Regarding the incidence of OH in normal body weight and obese patients, there was also no statistically significant difference. Conclusion: As shown in this study, trandolapril, along with some other ACE inhibitors, has shown good balance in hypertension control and OH occurrence.